pembatasan Pembatasan Sosial Bersekala Besar Dalam Perspektif Hukum Islam - moh Moh Numan; Afrohatul Laili Afrohatul Laili (Universitas Nahdlatul Ulama Blitar, 2022)
Large-Scale Social Restrictions or better known as PSBB (Pembatasan Sosial Berskala Besar) is one of the government policies taken to tackle the Covid-19 outbreak from the earth of Indonesia, this policy was taken with the consideration that health factors are the main factors that must be immediately addressed and prioritized over other factors, so that when the health factor has recovered, it will soon be able to build other state sectors such as the social, economic and education sectors which are heavily affected by this policy. This policy was taken with all its controversies because it collided directly with the economic sector, especially for small people who rely on their economy from daily income selling small items on the street. Of course, the policy needs ethical justification in order to become an effective policy, or if this policy is not in line with the public interest of the community, especially the small people, then the people can be ethically justified for what they do in response to this rule in the perspective of Islamic law.